2022
DOI: 10.1021/acsomega.2c06570
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Syn/Anti Relative Configuration of Cryptophane-222 on the Binding Affinity of Cesium and Thallium

Abstract: We report in this article the synthesis, the X-ray crystal structure of compound syn-2, and its binding properties with cesium and thallium in aqueous solution under basic conditions. Compound syn-2 is the diastereomeric compound of anti-1 that shows very high affinity for cesium and thallium in aqueous solution under the same conditions. Despite the close structural similarities that exist between the syn-2 and anti-1 compounds, they show large discrepancy in their ability to bind cesium and thallium cations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In another study by Brotin et al the syn-isomer 48 underwent hydrogenolysis in 83 % yield and 53 was used to study the binding properties with Cs + and Tl + ions (Scheme 7b). [54] Berthault et al transformed the syn-isomer 48 in to a watersoluble hexacarboxylic acid substituted cryptophane 54 in a stepwise manner, using methyl bromoacetate. [55] The syn-54 displays a high binding constant towards Xe.…”
Section: Synthesis Of Cryptophanes By the Template Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study by Brotin et al the syn-isomer 48 underwent hydrogenolysis in 83 % yield and 53 was used to study the binding properties with Cs + and Tl + ions (Scheme 7b). [54] Berthault et al transformed the syn-isomer 48 in to a watersoluble hexacarboxylic acid substituted cryptophane 54 in a stepwise manner, using methyl bromoacetate. [55] The syn-54 displays a high binding constant towards Xe.…”
Section: Synthesis Of Cryptophanes By the Template Methodsmentioning
confidence: 99%
“…In another study by Brotin et al . the syn ‐isomer 48 underwent hydrogenolysis in 83 % yield and 53 was used to study the binding properties with Cs + and Tl + ions (Scheme 7b) [54] . Berthault et al .…”
Section: Synthesis Of Cryptophanes By the Template Methodsmentioning
confidence: 99%
“…Our previous work revealed that the presence of hydroxyl functions was mandatory to sequester these two species, and that complexation efficiency increased with the number of hydroxyl functions [6c–e] . Moreover, increasing the size of the cavity decreased the complexation efficiency [6a,c] . Thus, the anti ‐cryptophane 1 ( D 3 ‐symmetry) decorated with six hydroxyl functions shows higher binding constants in basic solutions whereas the anti ‐cryptophane 2 ( C 3 ‐symmetry) decorated with six OCH 2 COOH groups was unable to bind cesium in the same conditions (Figure S17 in Ref.…”
Section: Introductionmentioning
confidence: 96%
“…Their ability to encapsulate a large range of atoms and molecules, neutral or charged, aroused people interest and contributed significantly to the development of these host cage-systems. They are able to encapsulate neutral guests, such as CH 2 Cl 2 /CHCl 3 [11] or methyloxirane [12][13][14], and charged species, such as Cs + /Tl + [15][16][17][18][19], in organic solutions as in aqueous ones. In addition, xenon is another guest of high interest that can enter the cavity of small cryptophanes.…”
Section: Introductionmentioning
confidence: 99%